Optimizacion de la composicion del atrayente sexual de Sesamia nonagrioides Lef. - Riba, M.=700 1 Sans, A.; Eizaguirre, M.; Perdiguer, A.; Gimeno, F.; Aguilar, L.
(En, Es)
ilus., 9 ref.
Keywords: SESAMIA NONAGRIOIDES; LEPIDOPTERA; NOCTUIDAE; MAIZ; ATRAYENTES SEXUALES; TRAMPAS; ESPAÑA